A short guide to writing about art - Barnet, Sylvan 1926-2016 (Pearson, 2015)
This book is intended for art courses where there is a writing component. This text guides art students through the writing process. Students are shown how to analyze pictures (drawings, paintings, photographs), sculptures and architecture. The text includes: coverage of essential writing assignments including formal analysis, comparison, research paper, review of an exhibition, essay examination; clear step-by-step writing instructions guiding students though the research and writing processes; sample essays, with analytic comments by the author, demonstrating the virtues of effective writing